2015
DOI: 10.4236/ojmc.2015.54005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrroles and Condensed Pyrroles as Anti-Inflammatory Agents with Multiple Activities and Their Molecular Docking Study

Abstract: We herein disclose a series of novel pyrrole derivatives as well as fused pyrrolopyridines 6a,b and 7a,b, pyrrolopyrazoles 8a, b, pyrrolo[2,3-d]pyrimidine derivatives 10a-d

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Moreover, the 2‐methyl‐4,8‐dioxotetrahydropyrido[1,2‐ b ]pyrimido[4,5‐ e ][1,2,4]triazepine derivative 6 was obtained via heating compound 2 in acetic anhydride/acetic acid mixture . The 13 C NMR spectrum of compound 6 displayed a signal at δ 22.50 ppm due to methyl carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the 2‐methyl‐4,8‐dioxotetrahydropyrido[1,2‐ b ]pyrimido[4,5‐ e ][1,2,4]triazepine derivative 6 was obtained via heating compound 2 in acetic anhydride/acetic acid mixture . The 13 C NMR spectrum of compound 6 displayed a signal at δ 22.50 ppm due to methyl carbon.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the 4‐amino‐2‐oxo‐dipyridotriazepine derivative 12 was prepared by refluxing an equimolar mixture of compound 2 and ethyl cyanoacetate in dimethylformamide containing triethylamine as a catalyst. 1 H NMR spectrum of compound 12 showed deuterium oxide exchangeable singlet signals at δ 5.65 and 8.48 ppm corresponding to pyridine–NH and OH–tautomeric protons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The classical NSAIDs inhibit both isoenzymes and their use is often accompanied by gastrointestinal intolerance [ 12 ], due to a decreased production of protective prostaglandin E2 in the stomach. New drugs that selectively inhibit COX-2 exhibit a better gastric tolerance profile [ 5 , 9 , 11 , 14 , 15 , 16 , 17 , 18 ]. Among well-known NSAIDs, pyrrole ring derivatives [ 19 ] are of remarkable interest [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several derivatives, including (S and a polar linking group (which attaches the aromatic ring to a lipophilic group in AA). 30 Addition of a second hydrophobic ring, not coplanar with the original aromatic ring, was found to enhance activity, 35 this second heteroaromatic ring or heterocyclic ring was believed to provide the necessary geometry to attach to AA. 81 Taking indomethacin (benzo[b] pyrrole) as an example, it was found that N-benzoyl moiety seems to play an important role for the COX-1 activity of indomethacin.…”
Section: Structure-activity Relationships (Sar)mentioning
confidence: 99%
“…[23][24][25][26][27][28] Pyrrolylacetic acid derivatives such as tolmetin (Rumatol ® ) and zomepirac (Zomax ® ) were proved to be NSAIDs 6 with strong anti-inflammatory activity. 29,30 Other pyrrole and fused pyrrole compounds have been recently reported as potent COX-1 and COX-2 inhibitors: 31,32 4-benzodioxine or pyrrole nucleus are described. All the newly synthesized compounds were examined for their in vitro and in vivo anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%